Spectrophotometric Determination of Tetracycline Hydrochloride in Pure Form and Pharmaceutical Preparation by Coupling with Diazotized Anthranilic Acid - Abd, Maryam Muhson; Dikran, Sarmad Bahjat; Mahmood, Ali Khalil (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A simple, fast and sensitive spectrophotometric method has been applied for the determination of tetracycline hydrochloride in its pure form and in pharmaceutical preparations. The method based on coupling reaction of the antibiotic with diazotized anthranilic acid to form a stable yellow azo dye which shows a maximum absorption at 419 nm. Uni- and multivariate approaches were followed in optimizing the experimental conditions. Under optimum experimental conditions obtained via multivariate (Central Composite Design), the linearity of the constructed calibration curve was in the range of 0.560 Î¼g.mL-1 with molar absorptivity of 14619 L.mol-1.cm-1 and the value of detection limit was 0.2813Î¼g.mL-1. The capability of the method for the analysis of real tetracycline samples was evaluated. The results show that the method could successfully be applied with no significant interference from the common excipients.